Baccharis dracunculifolia DC: Climate-Driven Metabolomic Variability in Essential Oils, Trichomes, and Antifungal Activity - Furlan, Paulo Henrique [UNESP]; Silva, Júlio C. R. L.; Facanali, Roselaine; Soares, Daniela M.; Cabral, Mariana Nunes Ferreira [UNESP]; Rodrigues, Tatiane Maria [UNESP]; Martins, Aline Redondo [UNESP]; da Gloria, Eduardo M.; Marques, Marcia O. M. (American Chemical Society (ACS), 2025)
Baccharis dracunculifolia DC. is a medicinal and aromatic plant species widely distributed in South America, predominantly in Brazil. It has been traditionally used in folk medicine and is the primary botanical source of Brazilian green propolis. The plant produces essential oils (EOs) in the glandular trichomes of its leaves, which exhibit pharmacological properties, including anti-inflammatory, antioxidant, and antimicrobial activities. Furthermore, these EOs also show potential for controlling agricultural pests and diseases. As a nondomesticated species, understanding its natural population dynamics and environmental adaptations is critical for selecting high-value genotypes and enhancing its commercial and ecological potential. This study investigated seasonal variation in glandular trichome density and EO chemical composition across dry and rainy seasons as well as their antifungal properties. While trichome density showed no significant seasonal variation, the EO yield increased during the rainy season (0.70 ± 0.16%). Comprehensive two-dimensional gas chromatography (GC×GC) analysis resulted in 88 compounds, with (E)-nerolidol, β-pinene, limonene, spathulenol, and bicyclogermacrene as the predominant constituents. Coelutions observed in one-dimensional GC were resolved using GC×GC, enabling the identification of minor season-specific compounds that chemically distinguished dry and rainy seasons. Antifungal assays revealed intrapopulation and seasonal variability in the inhibition of Fusarium graminearum, Fusarium verticillioides, and Aspergillus nomius. The compounds p-cymene, γ-muurolene, and α-cadinol exhibited the strongest correlation with the antifungal activity. The most successful EOs for antifungal activity were from genotypes 1BD02, against F. graminearum and A. nomius, and 1BD06, against F. verticillioides, both obtained in the dry season. These findings provide a framework for integrating ecophysiology and metabolomics to guide genotype selection of B. dracunculifolia.